Ambedkar and nation-building - Shyamlal, 1944-; Saxena, K. S.; National Seminar on "B.R. Ambedkar's Multi-Dimensional Aspects" (1998 : Academic Staff College, Jai Narain Vyas University) (Jaipur : Rawat Publications, 1998)
Consists twenty-three papers presented at a two-day National Seminar on "Dr. B.R. Ambedkar's Multi-Dimensional Aspects", held during Jan. 31-Feb. 1, 1998.
Includes bibliographical references.
Keywords: Ambedkar, B. R. -- 1891-1956 -- Political and social views -- Congresses